A practical atlas of congenital heart disease - Smith, Audrey; McKay, Roxane; Kirklin, John W; Kirklin, James K; Hajar Al Binali, Hajar Ahmed (Springer, 2004)
The atlas presents a comprehensive picture of congenital heart diseases. Intended for professionals.
Keywords: genetika, lékařská genetika; Heart Defects, Congenital; kardiologie; vrozené srdeční vady